The effects of different annealing temperature and number of deposition layers on the crystallographic properties of potassium sodium niobate (KNN) thin films synthesized by sol-gel spin coating technique - Akmal, M.H.M.; A. Rashid, M. W.; Azlan, U.A.A.; Azmi, N.A. (Journal of Advanced Manufacturing Technology (JAMT), 2017)
Potassium sodium niobate (KNN) thin films were successfully synthesized using the sol-gel spin coating method. X-ray diffraction (XRD) analysis was carried out to determine the crystallographic orientation and phase formation of thin films deposited at different annealing temperatures and a number of deposition layers. The XRD patterns and texture coefficient of the synthesized films confirmed that a highly oriented orthorhombic perovskite structure was obtained at 650 oC, while at higher temperature a spurious phase of K4Nb6O17 was evolved. The effective number of deposition layers was found to be five due to the formation of interconnected cracks at the six layered deposition. The XPPA analysis showed that the unit cell volume of the films was increased gradually from 110.83 cm3 at one layer to 124.31 at five layer deposition. Nevertheless, the lattice strain effect was small and negligible at high layer deposition due to the increased distance of the lattice with the film/substrate interface.